Prevalence and Associated Factors of Malnutrition among Children Aged 6-59 Months in Addi Harush Eritrean Refugees Camp, Tigray Region, North Ethiopia - Befekadu Ejigu; Tesfaye Girma Legesse; Daniel Haile Chercos (Journal of Pharmacy and Nutrition Sciences, 2017)
Malnutrition is a serious medical condition marked by a deficiency of energy, essential proteins, vitamins, and minerals in a diet. In Refugee situations where the population is often extremely dependent on the humanitarian assistance and food aid; the value of the food is greatly determine their nutritional status. That is why under nutrition is a critical public health problem among refugee children aged 6-59 months. Institutional based cross- sectional study was conducted from March to June, 2015 in Addi Harush Refugee camp, Northern Ethiopia. The data was collected using interview administered questioners, observational and Anthropometric measurement. Among the total of 372 planed participants 367 of them were enrolled in the study with a response rate of 98.7%. This had identified 69 (18.80%) of stunting and 36 (9.81%) of wasting. Children who fed exclusive breast feeding for the duration of six months were 0.04 times less likely to be wasted. Children, those who used bottle feeding were 6.067 times more likely to be affected with acute malnutrition (wasting). Children who had been vaccinated with BCG were 0.037 times less likely to be wasted. While generally immunized children were 0.013 times less likely to be wasted and 0.054 times less likely to be stunted. Both stunting and wasting are remaining public health nutrition problem in the refugee. Wasting is observed to be affected by immunization practice behavior, duration of exclusive breast feeding, BCG vaccination and bottle feeding. Stunting is observed to be affected by hand washing practice before serving food and immunization practice behaving. Bottle feeding should be avoided, Exclusive breast feeding till six months should be strengthen, Child immunization should be encouraged more than the current and Awareness towards cause and prevention of stunting and wasting should be increased at a refugee communities level.